Radiomics in diffusion data: a test–retest, inter- and intra-reader DWI phantom study. Issue 10 (October 2020) - Dreher, C.; Kuder, T.A.; König, F.; Mlynarska-Bujny, A.; Tenconi, C.; Paech, D.; Schlemmer, H.-P.; Ladd, M.E.; Bickelhaupt, S.
Abstract : AIM: The aim of this study was to evaluate the robustness of radiomics features of a MRI (magnetic resonance imaging) phantom in quantitative diffusion-weighted imaging (DWI) and depending on the image resolution. MATERIALS AND METHODS: Scanning of an in-house developed DWI phantom was performed at a 1.5 T MRI scanner (Magnetom AERA, Siemens, Erlangen, Germany) using an echo planar imaging (EPI) DWI sequence (b=0, 500, 1, 000 s/mm 2 ) with low (3×3 mm 2 ) and high (2×2 mm 2 ) image resolutions. Scans were repeated after phantom repositioning to evaluate retest reliability. Radiomics features were extracted after semi-automatic segmentation and standardised pre-processing. Intra-/interobserver reproducibility and test–retest robustness were assessed using intraclass correlation coefficients (ICC). Differences were tested with non-parametric Wilcoxon's signed-rank and Friedman's test ( p  < 0.05) with Dunn's post-hoc analysis. RESULTS: Test–retest ICC was overall high with >0.90 for 39/46 radiomics features in all sequences/resolutions. Decreased test–retest ICCs were pronounced for conventional Min-value (overall ICC=0.817), and grey-level zone length matrix (GLZLM) features Short-Zone Emphasis (SZE) and Short-Zone Low Grey-level Emphasis (SZLGE) (for both overall ICC=0.927). Test–retest reproducibility was significantly different between b=500, 1, 000 and apparent diffusion coefficient (ADC) (mean 0.975±0.050, 0.974±0.051 and 0.966±0.063), which remained significant after post-hoc analysis between b=1, 000 and ADC ( p = 0.022). ICCs were not significantly different between resolutions of 2×2 and 3×3 mm 2 regarding b=500 (mean: 0.977±0.052 and 0.974±0.049, p = 0.612), b=1, 000 (mean: 0.973±0.059 and 0.974±0.054, p = 0.516), and ADC (mean: 0.972±0.049 and 0.955±0.101, p = 0.851). Inter- and intra-observer reliability was consistently high for all sequences (overall mean 0.992±0.021 and 0.990±0.028). CONCLUSION: Under ex-vivo conditions, DWI provided robust radiomics features with those from ADC being slightly less robust than from raw DWI (b=500, 1, 000 s/mm 2 ). No significant difference was detected for different resolutions. Although, ex-vivo reliability of DWI radiomics features was high, no implications can be made regarding in-vivo analyses. Highlights: Radiomics features of DWI and ADC are highly reliable with this ex-vivo approach. Radiomics features of ADC are less robust than those extracted from raw DWI images. DWI with different matrix sizes provides similar reliability of radiomics features.